IDE PEMIKIRAN MODERNISME SYEIKH MOHAMMAD ABDUH DALAM PEMBENTUKAN MUHAMMADIYAH - Abd. Rahman A. Ghani; Moh Suryadi Syarif; Jeanne Francoise (Jurnal PGSD, 2020)
Ontologically, Muhammadiyah is not only a foundation, but an idea of ??a modern Islamic movement and a respected Islamic community in Indonesia. Epistemologically, Muhammadiyah's modern Islamic thought is manifested in the field of education, by including the national curriculum. Then axiologically, Muhammadiyah not only educates Muslims, but also internalizes aspects of peace and progress for the entire Indonesian nation, so that a Muhammadiyah cadre is expected to become a form of peace itself. This article will describe in more depth Muhammadiyah as a modern educational institution. To analyze this, this paper uses Syeikh Muhammad Abduh's modern Islamic thinking and Muhammadiyah's unique values. The research was conducted using qualitative research methods through literature study. The research findings are about the relationship between Muhammad Abduh's ideas of Islamic modernism which influenced K.H. Ahmad Dahlan to form Muhammadiyah, and how these ideas will continue to be updated along with the times. This paper is expected to add to the wealth of insights about Muhammadiyah and can be a reference for further research for cadres of teachers and lecturers in the academic environment of Prof. Dr. HAMKA (UHAMKA). Keywords: Muhammadiyah; Indonesia; Pancasila; Uhamka; Abduh